Avoid a Fall or Fly Again : Turning Points of State Fragility - Akanbi, Olusegun Ayodele (IMF Working Papers; Working Paper, 2021)
High persistence of state fragility (a fragility trap) suggests the presence of substantial benefits from avoiding a fall into fragility and considerable hurdles to successful exit from fragility. This paper empirically examines the factors that affect the turning points of entering and exiting from state fragility by employing three different approaches: an event study, the synthetic control method, and a logit model. We find that avoiding economic contraction is critical to prevent a country on the brink of fragility from falling into fragility (e.g., among near fragile countries, the probability of entering fragility would rise by 40 percentage points should real GDP per capita growth decline from +2.5 percent to -2.5 percent). Also, strengthening government effectiveness together with increasing political inclusion and maintaining robust economic activity should help make exit from fragility more successful and sustainable. In the current environment (the COVID-19 crisis and its aftermath), the findings suggest the importance of providing well-directed fiscal stimulus with sufficient financing, (subject to appropriate governance safeguards and well-designed policies), and protecting critical socio-economic spending to keep vulnerable countries away from being caught in a fragility trap.